Tomato Varietal and Insecticidal Screening against Greenhouse Whitefly Trialeurodes vaporariorum Westwood under Poly-House Condition - Upadhaya, Sudeep Kumar; Chiluwal, Kashinath; Bhusal, Bikash (Journal of the Plant Protection Society, 2024)
Greenhouse whitefly (GHW) (Trialeurodes vaporariarum Westwood) is a serious vector pest of tomato viral diseases. Eight commercial varieties including Pusa Ruby as a check were subjected to varietal screening tests. Similarly, screening of six insecticides against GHW on the most susceptible variety, Pusa Ruby was carried out. Both the experiments were carried out in 2020 and 2021 under poly house condition at Khumaltar, Lalitpur, Nepal. Check variety Pusa Ruby proved to be the most susceptible for GHW as it harbored the highest number of both nymphs (F7, 16 = 7.81, P < 0.01) and adults (F7, 16 = 10.77, P < 0.01). In insecticidal screening tests, all the potential insecticides; neemex, Verticillium lecanii, imidacloprid, spiromesifen, nitenpyram and thiamethoxam were found equally and highly significantly effective against the GHW as compared to the control during both years. This study suggested to consider the tested insecticides of their commercial formulation and claimed application doses for the management of GHW in tomato plants.